Genotype and Phenotype Analysis of Chinese Children With Tuberous Sclerosis Complex: A Pediatric Cohort Study - Ding, Yifeng; Wang, Ji; Zhou, Shuizhen; Zhou, Yuanfeng; Zhang, Linmei; Yu, Lifei; Wang, Yi (Frontiers in Genetics, 2020)
Tuberous sclerosis complex (TSC) is a genetic condition characterized by the occurrence of hamartomatous wounds stemming from the dysfunction of the mammalian target of rapamycin (mTOR) pathway. We investigated the clinical phenotypes and genetic variants in 243 unrelated probands and their families in China. Exome sequencing, targeted sequencing or multiplex ligation-dependent probe amplification (MLPA) was performed in 174 children with TSC, among whom 31 (17.82%) patients/families were identified as having pathogenic or likely pathogenic variants in the TSC1 gene, 120 (68.97%) as having pathogenic or likely pathogenic variants in the TSC2 gene and 23 (13.21%) as having no pathogenic or likely pathogenic variants identified (NMI). In the 31 patients with pathogenic or likely pathogenic TSC1 variants, 10 novel variants were detected among 26 different variants. In all 120 patients with TSC2 variants, 39 novel variants were found among a total of 107 different variants. We compared the phenotypes of the individuals with TSC1 pathogenic variants, TSC2 pathogenic variants and NMI. Patients with TSC2 variants were first diagnosed at a younger age (p=0.003) and had more retinal hamartomas (p=0.003) and facial angiofibromas (p=0.027) (age≥3 years) than individuals with TSC1 variants. Compared with individuals with TSC1/TSC2 pathogenic variants, NMI individuals had fewer cortical tubers (p=0.003). Compared with individuals with TSC1 pathogenic variants, NMI patients had more retinal hamartomas (p=0.035), and compared with individuals with TSC2 pathogenic variants, they had less epilepsy (p=0.003) and fewer subependymal nodules (SENs) (p=0.004).